(untitled) (Orthodontic Journal of Nepal, 2015)
Introduction: Reinfection of root canal treated tooth leads to endodontic failure. In such case surgical endodontic therapy is the treatment of choice which provides obturation of radicular space with 3-dimensional sealing. Objective: To evaluate and compare the sealing ability of Mineral trioxide aggregate (MTA) with Glass ionomer cement (GIC) and Super EBA (Epoxybenzoic acid) root-end filling materials. Materials & Method: 94 extracted single rooted upper anterior teeth were selected for root canal preparation and obturation. Root were apically resected 3 mm; and 3 mm deep Class-I root-end cavities were prepared. Teeth were randomly distributed into 3 groups comprising 30 teeth in each group. Group-1 was retrofilled with MTA, Group-2 with GIC and Group-3 with Super EBA. 2 positive and 2 negative control teeth were instrumented and obturated but not filled on root-end cavity. In experimental groups and positive control group the whole surface of teeth except 3 mm adjacent to resected area were covered with two coats of nail polish but in negative control group whole surface of teeth were covered, dried, immersed in 1% methylene blue for 72 hours. Each root was sectioned labio-lingually to the long axis of root. Depth of dye penetration was evaluated by 10x stereo-microscope. Result: MTA retrograde filling showed the best hermetic seal property whereas, few GIC and Super EBA samples showed microleakage in retrograde filling. GIC showed better sealing ability than Super EBA. Conclusion: MTA has potential to provide better hermetic-seal than GIC and Super EBA as root-end filling material.